2020
DOI: 10.1088/1751-8121/abab54
|View full text |Cite
|
Sign up to set email alerts
|

Trigonometric SU(N) Richardson–Gaudin models and dissipative multi-level atomic systems

Abstract: We derive the exact solution of a system of N -level atoms in contact with a Markovian reservoir. The resulting Liouvillian expressed in a vectorized basis is mapped to an SU (N ) trigonometric Richardson-Gaudin model whose exact solution for the complete set of eigenmodes is given by a set of non-linear coupled equations. For N = 2 (SU (2)) we recover the exact solution of Phys. Rev. Lett. 122, 010401 (2019). We then study the SU (3) case for three-level atom systems and discuss the properties of the steady s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
(96 reference statements)
0
6
0
Order By: Relevance
“…In this sector and for two replicas, the on-site representation is the [6] representation of sl( 4) or so (6), that of rank 4 anti-symmetric tensors of sl( 4) or that of 6-dimensional vectors of so (6). We have the decomposition rule, [20] as sl( 4) or so( 6) modules, with [15] the rank two antisymmetric so (6) tensors and [20] the rank two traceless symmetric so( 6) tensors. The projectors on these representations are (with d = 6)…”
Section: It Is the Sl(2rmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sector and for two replicas, the on-site representation is the [6] representation of sl( 4) or so (6), that of rank 4 anti-symmetric tensors of sl( 4) or that of 6-dimensional vectors of so (6). We have the decomposition rule, [20] as sl( 4) or so( 6) modules, with [15] the rank two antisymmetric so (6) tensors and [20] the rank two traceless symmetric so( 6) tensors. The projectors on these representations are (with d = 6)…”
Section: It Is the Sl(2rmentioning
confidence: 99%
“…The simplest such class of Lindblad equations can be mapped to imaginary-time Schrödinger equations with non-Hermitian "Hamiltonians" that are quadratic in creation/annihilation operators [8][9][10][11]. More recently it has been shown that there exist Lindblad equations whose evolution operators are related to interacting integrable quantum spin chains [12][13][14][15][16][17][18][19][20][21][22][23][24]. This opens the door to obtaining exact results on the average dissipative dynamics of many-particle Lindblad equations by employing methods from quantum integrability.…”
Section: Introductionmentioning
confidence: 99%
“…Another class of solvable Lindblad equations are "triangular" models which add particle loss and dephasing terms to otherwise number conserving integrable models [31,32,33]. Recently a new direction for constructing solvable many particle Lindblad equations was identified through the discovery of Lindblad equations that can be related to interacting Yang-Baxter integrable models [34,35,36,37,38,32,33,39,40,41,42]. The approach of Refs [34,38] is based on a superoperator representation of the Lindblad equations, which gives rise to solvable "two-leg ladder" quantum spin chain models.…”
Section: Introductionmentioning
confidence: 99%
“…This system is a particular limit of the Richardson-Gaudin model and has been solved exactly in Refs. [25,26]. It is relevant for the study of quantum cavity electrodynamics [27,28], magnetic grains on a metallic surface [24], or superconducting quantum circuits [29].…”
mentioning
confidence: 99%